The Effect of Profitability, Transfer Pricing, and Capital Intensity on Tax Avoidance in Property and Real Estate Companies Listed onThe Indonesia Stock Exchange For The 2021-2023 Period - Aisah, Nur; Setiany, Erna (Universitas Mercu Buana, 2024)
This study aims to analyze the effect of profitability, transfer pricing, and capital intensity on tax avoidance in property and real estate companies listed on the Indonesia Stock Exchange (BEI). The research population consists of 92 companies, with a sample of 35 companies selected based on specific criteria. The sample includes companies listed on the IDX during the 2021-2023 period, using Rupiah as the currency in their financial statements, and having submitted annual financial reports containing relevant data and information for this study. Additionally, the financial statements used have been audited and accompanied by an independent auditor's report. The sampling method employed in this study is purposive sampling, while the data collection method is documentation, which involves gathering materials or data related to the research object. The data analysis technique used is descriptive statistical analysis. The results of the study indicate that capital intensity has the strongest influence on tax avoidance. Capital intensity has a positive and significant effect on tax avoidance in property and real estate sub-sector companies listed on the IDX during the 2021-2023 period. Meanwhile, profitability has a negative and significant effect on tax avoidance, meaning that the higher the profitability of a company, the lower its level of tax avoidance. A similar pattern is observed in transfer pricing, where the study results show that transfer pricing has a negative and significant effect on tax avoidance in the property and real estate sub-sector companies during the same period.